IDENTIFICATION AND PHENOTYPIC CHARACTERISTICS OF LACTIC ACID BACTERIA ISOLATED FROM SOME TRADITIONAL CHEESES PRODUCED IN THE REPUBLIC OF MACEDONIA - Vesna Levkov; Sandra Mojsova; Rodne Nastova; Sonja Srbinovska; Natasha Gjorgovska (Institute of Animal Science-Skopje, 2017)
characteristics of lactic acid bacteria isolated from beaten cheese and white brined cheese produced from raw ewe’s milk in traditional way were object of this study. From all the stages of beaten cheese manufacturing, 240 isolates were isolated. According to the phenotypic and biochemical characteristics, the prevailing species were Lactococcus lactis spp. lactis (35%), Lactobacilus paracasei subsp. paracasei (22.5%), Pediococcus sp. (16.7%), L. plantarum (15.8%), L. brevis (9.17%) and Leuconostoc sp. (1%). From white brined cheese 39 isolates were isolated belonging to the genera Lactobacillus (59%), Enterococcus (23.1%) and Leuconostoc (17.9%), The prevalent species were identified as: E. durans, Leuconostoc mesenteroides subsp. Mesenteroides /dexstranicum, Lactobacillus plantarum and L. curvatus, mostly isolated in the early stages of cheese’s ripening, and L. plantarum and L. paracasei subsp. paracasei isolated from ripened cheese samples. In both cheese types dominant species were mesophilic lactic acid bacteria characteristic for brined cheeses from north-eastern Mediterranean and Balkan countries.
Keywords: lactic acid bacteria; phenotypic and biochemical characteristics; traditional cheese